PENELUSURAN BANJIR SUNGAI LUK ULO AKIBAT PERUBAHAN TUTUPAN LAHAN - Budiyanto, Muchamad Arif (Universitas Negeri Semarang, 2017)
River is the most important source of water and its benefits are needed by all levels of society, directly or indirectly. The river control is essentially an effort to obtain the greatest benefit and reduce the damage or loss to minimum. Highly dynamic socio-economic development in Indonesia impact on various components of the community environment, one of which is land use change from time to time. Research of landused changes made in Luk Ulo Watershed (DAS) in line with the development of Kebumen district.In this research of flood routing due to changes in landused are known of analysis flood discharge, one of which is the method “Soil Conservation Service Hydrograf Unit: (SCS-UH). In this research, conducted flood routing of Luk Ulo watershed due to changes in land use on 2009 and 2015. The method used in this research is the method SCS-UH by assessing changes in the value of Curve Number (CN).This research was conducted assessment parameters on Luk Ulo watershed land used by Watershed rainfall with a specific return period. From the analysis obtained changes in the area in the form of open field in the amount of 945.52 ha. From the discharge analysis there are no significant changes in flood peak, only the addition of 2.89 m3 / sec. These results indicate the method by only using SCS - curve number show unsignificant results. preferably coefficient of land cover assessment should be obtained from the measurement results on the field as verification on watershed conditions.